Indonesia’s counter-terrorism policy, 2001 –2009 - Abdel Salam, El Fatih Abdullahi (2014)
Consecutive terror attacks and the suicide bombings at the J.W. Marriott Hotel and Ritz-Carlton Hotel in Jakarta on July 17th, 2009, indicate that terrorism remains a serious security threat to the world’s biggest Muslim country, Indonesia. This study attempts to analyze the politics of the Indonesian government’s response to terrorism during the period 2001—2009. It asks three interrelated questions. Firstly, according to the government’s perspective, who was responsible for the major bomb attacks in Indonesia? Secondly, what sort of counterterrorism policies did the government make? Finally, what are the main factors that shaped the government’s counterterrorism policy during that period? To explain the Indonesian government’s counterterrorism policy, this study adopts “the logic of two-level games” (Putnam, 1988) as the theoretical framework. The “two-level games” perspective suggests that government policy is a function of incentives and constraints both at the international and the domestic level. As gatekeepers between the two levels, governments simultaneously process these interdependent incentives and constraints in their policy decision-making. They balance between potentially conflicting international and domestic pressures and attempt to formulate and implement policies that satisfy both. The data used in this research are mostly derived from official documents, direct interviews with government officials and the secondary sources (books and journals) on terrorism and counterterrorism. This study shows that, although it never banned Al-Jamaah Al-Islamiyah (AJAI) because of domestic considerations, the government believes that the AJAI is a terrorist network mostly responsible for the consecutive bombings in Indonesia. Secondly, different from policy of the previous regime, the government has mostly relied on a “law-enforcement approach” in denting the terrorist network which has been incrementally complemented with an “ideological approach” to fight religious extremism. Finally, the pathway of Indonesia’s counterterrorism policy was shaped by contradictory pressures originating from the Muslim community and human rights groups in the domestic political environment, on one hand, as well as international pressures originating from the United States and its allies, on the other hand. Societal pressures constrain the government’s freedom to manoeuvre in adopting policy, whereas international pressures bolster the government’s determination and capability to fight terrorism. The government seeks to achieve a balance between the two conflicting pressures and attempts to adopt and implement policies that satisfy both conflicting forces. This study attempts to fill the gap in the existing works on terrorism and counterterrorism in Indonesia. It analyzes the core elements of the government’s counterterrorism policy and locates them within the context of contradictory pressures originating from societal/domestic political forces and international forces.